VITAMIN D DEFICIENCY IN PATIENTS WITH PSORIASIS AND PSORIATIC ARTHRITIS - Q MOHAMMED, JINAN; MATHKHOR, ABDULSATAR J; S KHUDHAIRY, AMER (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of this study is to investigate the association between Vitamin D level and psoriasis, in particular in our city of the long, hot, and sunny weather, in an attempt to add a clarification to this controversial subject. Methods: A case–control study included 120 patients with psoriasis and 38 patients with psoriatic arthritis (PsA); 89 (56.3%) patients were male. Psoriasis area and severity index (PASI) was calculated for all patients with psoriasis and disease activity score using 28 joints (DAS28) and erythrocyte sedimentation rate (DAS28) was measured for all patients with PsA. The control group comprised 164 age- and sex-matched participants (91 males and 73 females). Vitamin D serum level was performed for both patients and controls. Results: Vitamin D levels in both patients and controls were 17.4±7.7 and 28.3±5.6, respectively. The level of Vitamin D was lower in a patient with disease duration equal and more than 10 years than those with a disease duration <10 years. There is no significant difference in Vitamin D levels between the two patient subgroups. Lower Vitamin D levels were associated with high PASI and high DAS28 in psoriasis and PsA, respectively. Conclusion: Patients with psoriasis and PsA associated with low levels of serum Vitamin D. Vitamin D deficiency was found to be associated with long disease duration in both psoriasis and PsA. Patients with active disease have lower Vitamin D levels.